THE ROLE OF CONGREGATIONAL DHUHA PRAYER ACTIVITIES IN FORMING STUDENTS' SPIRITUAL CHARACTER - Hendro Juwono; Muhammad Zamroni (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze the role of congregational Dhuha prayer activities in  shaping students’ spiritual character  . The background of this  research is based on the importance of developing religious character through the  habituation of worship as an integral part of Islamic education. The research  employed a qualitative approach with data collection techniques including  observation, interviews, and documentation. The research was conducted at   Anshoriyah, Parijata Wetan Village. Data were analyzed using an interactive  analysis model, consisting of data reduction, data display, and conclusion drawing.  The findings revealed that the implementation of congregational Dhuha prayer  significantly contributes to the development of students’ spiritual character.  Regular and structured worship activities foster religious values reflected in  positive behavioral changes among students. The observed impacts include  increased punctuality, personal responsibility, emotional calmness, politeness and  social empathy, as well as enhanced awareness of worship and gratitude to Allah.  Supporting factors for this activity include strong commitment from the principal  and teachers, adequate mushalla facilities, and continuous guidance. Meanwhile,  inhibiting factors include limited awareness among some lower-grade students and  the need to strengthen worship motivation. The habituation of congregational  Dhuha prayer serves as an effective strategy for strengthening students’ spiritual  character and is worthy of implementation as a religious culture development  program in Islamic elementary schools.